2021
DOI: 10.3389/fmed.2021.729300
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-Responsive Nanoplatform-Assisted Photodynamic Therapy Against Bacterial Infections

Abstract: Bacterial infections are common diseases causing tremendous deaths in clinical settings. It has been a big challenge to human beings because of the antibiotics abuse and the newly emerging microbes. Photodynamic therapy (PDT) is a reactive oxygen species-based therapeutic technique through light-activated photosensitizer (PS). Recent studies have highlighted the potential of PDT as an alternative method of antibacterial treatment for its broad applicability and high efficiency. However, there are some shortcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Another promising idea, which is based on the synergistic effect of nanomaterial-based strategies with antibiotics, is provided by antibacterial photodynamic therapy (aPDT). In general, PDT induces reactive oxygen species (ROS) by using a light-activated photosensitizer [ 287 ]. Recently, it was reported that the photosensitizer, that is, 5, 10, 15, 20-Tetrakis(3-hydroxyphenyl)chlorin (temoporfin), suppressed the expression of the antibiotic resistance gene mecA (encoding PBP2a) and considerably reduced MRSA drug resistance.…”
Section: At the Dawn Of The Post-antibiotic Era?mentioning
confidence: 99%
“…Another promising idea, which is based on the synergistic effect of nanomaterial-based strategies with antibiotics, is provided by antibacterial photodynamic therapy (aPDT). In general, PDT induces reactive oxygen species (ROS) by using a light-activated photosensitizer [ 287 ]. Recently, it was reported that the photosensitizer, that is, 5, 10, 15, 20-Tetrakis(3-hydroxyphenyl)chlorin (temoporfin), suppressed the expression of the antibiotic resistance gene mecA (encoding PBP2a) and considerably reduced MRSA drug resistance.…”
Section: At the Dawn Of The Post-antibiotic Era?mentioning
confidence: 99%
“…In another work, emodin-chitosan NPs were designed as PS in aPDT therapy against S. mutans biofilm on the enamel surface ex-vivo [ 223 ]. To improve the antimicrobial specificity and selectivity, stimuli-responsive nanoplatforms have been proposed to enhance the delivery of PS [ 261 ]. Different signals from pH levels, enzymes, redox, magnetic, and electric have been used and reviewed here [ 261 ].…”
Section: Smart Dental Materials For Antimicrobial and Antibiofilm The...mentioning
confidence: 99%
“…To improve the antimicrobial specificity and selectivity, stimuli-responsive nanoplatforms have been proposed to enhance the delivery of PS [ 261 ]. Different signals from pH levels, enzymes, redox, magnetic, and electric have been used and reviewed here [ 261 ]. For example, in dentistry, magnetic fields have been used in the targeted delivery of magnetic materials.…”
Section: Smart Dental Materials For Antimicrobial and Antibiofilm The...mentioning
confidence: 99%
“…Even undergoing mutations, it is hard for bacteria to evade ROS-mediated ablation because ROS oxidation can act on multitargets, leading to resistance loss. 8 Benefiting from the role of ROS in the immune defense mechanism against bacteria, bacterial infections can be potentially treated by improving ROS generation or interfering with ROS defense mechanisms. 9 Photosensitizers (PSs) can produce ROS under appropriate light stimulation for broad-spectrum treatment of bacteria and reduce bacterial resistance concerns, making antibacterial photodynamic therapy (APDT) a potential alternative antibacterial modality.…”
Section: Introductionmentioning
confidence: 99%